Characterization and source identification of tetracycline antibiotics in the drinking water sources of the lower Yangtze River. (15th August 2019) - Wang, Zhiyuan; Chen, Qiuwen; Zhang, Jianyun; Dong, Jianwei; Yan, Hanlu; Chen, Cheng; Feng, Ranran
Abstract: The occurrence and spatio-temporal patterns of five tetracyclines (TCs) and six of their degradation products were investigated in twenty-eight drinking water sources along the lower Yangtze River (LYR) over dry, normal and flood seasons. Tetracycline (TC), oxytetracycline (OTC) and doxytetracycline (DXC) were the dominant antibiotics detected with the highest occurrence. The maximum concentrations of TC, OTC and DXC were found in dry season as 11.16, 18.98, and 56.09 ng/L, respectively, because of the low dilution, low degradation, and high consumption in this season. Cluster analysis indicated distinct variations in the TCs' compositional profiles in both space and time. OTC and its metabolites contributed 18.5–59.6% of the TC load in dry season, possibly due to the seasonally increased release of pharmaceutical OTCs from sewage effluents, but they were seldom detected in other seasons. Pollution load index analysis showed that tributaries carrying large amounts of veterinary TCs derived from breeding wastewater and untreated rural sewage contributed larger proportions of the TC load for most drinking water sources than sewage outlets. The contribution ratio of the TC load from tributaries (74.5%) was approximately three times higher than that from sewage discharges (25.5%). The study demonstrated that the control of load from tributaries is the key to mitigating TC pollution of the drinking water sources in the LYR. An effective source tracking method for evaluating the contribution of antibiotic load from multiple diffuse pollution origins and identifying the high-risk contamination sources was established for antibiotic management and control. Graphical abstract: Image 1 Highlights: Low flow, low degradation and high emission caused high content of TCs in winter. Tributaries contributed three times higher load of TCs than sewage effluents. Veterinary load from tributaries elevates human exposure to TCs via drinking water. Method to identify major contamination sources was provided for antibiotic control.